2016
DOI: 10.1038/srep39399
|View full text |Cite
|
Sign up to set email alerts
|

The human intestinal microbiota of constipated-predominant irritable bowel syndrome patients exhibits anti-inflammatory properties

Abstract: The intestinal microbiota of patients with constipated-predominant irritable bowel syndrome (C-IBS) displays chronic dysbiosis. Our aim was to determine whether this microbial imbalance instigates perturbation of the host intestinal mucosal immune response, using a model of human microbiota-associated rats (HMAR) and dextran sulfate sodium (DSS)-induced experimental colitis. The analysis of the microbiota composition revealed a decrease of the relative abundance of Bacteroides, Roseburia-Eubacterium rectale an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 49 publications
3
62
1
1
Order By: Relevance
“…in individuals with PD. Enrichment in Akkermansia muciniphila is known to be related to longer gastrointestinal passage times . However, we did not find Akkermansia abundances to be related to self‐reported constipation.…”
Section: Discussioncontrasting
confidence: 88%
“…in individuals with PD. Enrichment in Akkermansia muciniphila is known to be related to longer gastrointestinal passage times . However, we did not find Akkermansia abundances to be related to self‐reported constipation.…”
Section: Discussioncontrasting
confidence: 88%
“…Experiments with the GABAb agonist baclofen have shown that GABAb receptors can reduce gastric mobility in the colon of rabbits (via cholinergic modulation) (Tonini et al 1989). Interestingly, A. muciniphila has been shown to be positively associated with gastrointestinal transit time (Gobert et al 2016; Vandeputte et al 2016). GABA could reach the CNS via blood stream as a lipophilic compound, being able to pass the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Mono-association of Il10 -/mice with A. muciniphila did not induce signs of intestinal inflammation within three weeks but only mildly activated the immune response based on slightly increased fecal lipocalin-2 concentrations. This result indicates that A. muciniphila did not disturb gut immune homeostasis but was perceived as a non-inflammatory, commensal bacterium by the host immune system as observed for wild type mice, 43 even if the host, the Il10 -/mouse, was genetically predisposed to developing colitis. 20 Indeed, mono-association of NMRI wild type mice with A. muciniphila induces the expression of genes involved in antigen presentation in cecum and upregulates the expression of genes involved in innate and adaptive immune responses in the colon without inducing a pro-inflammatory response in these mice.…”
Section: Discussionmentioning
confidence: 60%
“…These cell numbers are approximately one order of magnitude higher than those detected in humans but in the same range as those reported for monoassociated wild-type mice. 2,43 This suggests that the lack of a pro-inflammatory effect of A. muciniphila is not due to an insufficient colonization efficiency of the A. muciniphila strain used in our experiments. It is important to note that we analyzed the short-term effect of A. muciniphila strain ATCC BAA-835 three weeks after its application.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation